A fast ray casting method for sound refraction at shear layers. Issue 1 (March 2017) - Sarradj, Ennes
The application of microphone arrays for aeroacoustic measurements in wind tunnels with an open test section requires to consider the sound refraction at the shear layer. Several methods are available for this that are either applicable to special scenarios such as planar or cylindrical thin shear layers or that require considerable computational effort. The paper concerns a new method for general application—ray casting—that is based on a ray tracing method. Ray tracing is briefly revisited and it is shown that the computational effort becomes quite high especially for large mapping grids. The ray casting approach with its interpolation technique is introduced. A time reversal technique is the key to make this approach very efficient and fast. Finally, the approach is demonstrated using two example results from simulation and from a practical measurement.